2021
DOI: 10.1002/qj.4179
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical propagation and growth mechanisms for convectively coupled equatorial Kelvin waves over the Indian Ocean

Abstract: Convectively coupled equatorial Kelvin waves (CCKWs) are high-impact tropical weather systems that can lead to severe flooding over the Maritime Continent. Here, a vorticity budget for CCKWs over the Indian Ocean is constructed using reanalysis data, to identify the basic mechanisms of eastward propagation and growth. The budget is reasonably well closed, with a small residual/subgrid-scale term. In the lower troposphere, CCKWs behave like strongly modified theoretical equatorial Kelvin waves. Vortex stretchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…The period of this global-scale oscillation is about 12.5 TRAPPIST-1e orbits, or approximately 76 Earth days. This rather long period as well as a preference toward positive zonal wavenumbers (not shown) makes the ExoCAM variability somewhat similar to the Madden-Julian Oscillations (MJO) observed on Earth (see, e.g., Madden & Julian 1971;Kiladis et al 2009;Matthews 2021). Faithful representation of the MJO remains a challenge even for sophisticated climate and weather models (Vallis & Penn 2020).…”
Section: Time Variabilitymentioning
confidence: 80%
“…The period of this global-scale oscillation is about 12.5 TRAPPIST-1e orbits, or approximately 76 Earth days. This rather long period as well as a preference toward positive zonal wavenumbers (not shown) makes the ExoCAM variability somewhat similar to the Madden-Julian Oscillations (MJO) observed on Earth (see, e.g., Madden & Julian 1971;Kiladis et al 2009;Matthews 2021). Faithful representation of the MJO remains a challenge even for sophisticated climate and weather models (Vallis & Penn 2020).…”
Section: Time Variabilitymentioning
confidence: 80%
“…In terms of Kelvin wave-driven convergence (negative divergence) acting on absolute vorticity 51 , both CCKW were important, but CCKW#2 was even more impactful than CCKW#1. Figure 7a, b shows the vortex stretching term—the interaction of absolute vorticity with low-level anomalous divergence associated with CCKWs.…”
Section: Resultsmentioning
confidence: 99%
“…This deflection was crucial for structuring the convection over Timor by positioning the CCKW westerly wind anomaly in the Java sea. Recently, Matthews 51 showed that the meridional gradient of the zonal wind anomaly results in significant relative vorticity south of a CCKW axis. This study shows that over the Indian Ocean, a major contribution to the vorticity tendency comes from CCKW divergence acting on background environmental vorticity.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum distance between the trajectories of the star and the Sun d min at the moment of approach t min is calculated based on the following relations (Matthews, 1994):…”
Section: Linear Methodsmentioning
confidence: 99%
“…The early history of searches for close encounters of stars with the Solar System using various catalogs is reflected in the works of Revina (1988), Matthews (1994), Mülläri, Orlov (1996), Garcia-Sánchez et al (1999;2001), Bobylev (2010a;2010b) , Anderson, Francis (2012), Dybczyński, Berski (2015), Bailer-Jones (2015), Feng, Bailer-Jones (2015). In particular, it was found that one of the record holders, a candidate for penetration into the Oort Cloud, is the star GJ 710 (Garcia-Sanchez et al, 2001;Bobylev, 2010a;Berski and Dybczyński, 2016).…”
Section: Introductionmentioning
confidence: 99%